Relationship Between Fear of COVID-19, Psychopathology and Sociodemographic Variables in Malaysian Population - Mohd Amiruddin Mohd Kassim; Nicholas Pang Tze Ping; Mohamed, N.H.; Assis Kamu; Ho Chong Mun; Ayu, F.; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Mohammad Saffree Jeffree (Springer, 2021)
COVID-19 has affected Malaysia in multitude aspects. Although Malaysia is on the right track to flatten the curve attributed to swift and decisive actions by the government, it is important to assess the psychological after effect that caused by the pandemic and the movement control order. This study performed in Borneo, Malaysia, was conducted using principles of snowballing, and by invitation through university students and staffs mailing list to participate. The survey collected data on sociodemographic, along with measuring psychological impact by using the newly validated Malay version Fear of COVID-19 Scale and DASS-21 scale. There were a total of 255 respondents. The majority of the respondents’ age was 25 years and below, with a female male ratio of 2:1 and around 70% respondents were students. Below 25-year-old age group, and females are having significantly higher levels of fear of COVID-19, depression, anxiety, and stress. Single people have higher depression level. There was a significant difference between students and non-students for depression, anxiety, and stress, but not for fear of COVID-19. It is imperative to allay the fears and psychological sequalae of COVID-19, especially those individuals at higher risks. Psychological interventions as well as telepsychiatry mobilisation could prove useful in dealing with the distress. © 2021, Springer Science+Business Media, LLC, part of Springer Nature.